Detection, eye–hand coordination and virtual mobility performance in simulated vision for a cortical visual prosthesis device - Srivastava, Nishant R (2009)
In order to assess visual performance using a future cortical prosthesis device, the ability of normally sighted and low vision subjects to adapt to a dotted ‘phosphene’ image was studied. Similar studies have been conduced in the past and adaptation to phosphene maps has been shown but the phosphene maps used have been square or hexagonal in pattern. The phosphene map implemented for this testing is what is expected from a cortical implantation of the arrays of intracortical electrodes, generating multiple phosphenes. The dotted image created depends upon the surgical location of electrodes decided for implantation and the expected cortical response. The subjects under tests were required to perform tasks requiring visual inspection, eye–hand coordination and way finding. The subjects did not have any tactile feedback and the visual information provided was live dotted images captured by a camera on a head-mounted low vision enhancing system and processed through a filter generating images similar to the images we expect the blind persons to perceive. The images were locked to the subject’s gaze by means of video-based pupil tracking. In the detection and visual inspection task, the subject scanned a modified checkerboard and counted the number of square white fields on a square checkerboard, in the eye–hand coordination task, the subject placed black checkers on the white fields of the checkerboard, and in the way-finding task, the subjects maneuvered themselves through a virtual maze using a game controller. The accuracy and the time to complete the task were used as the measured outcome. As per the surgical studies by this research group, it might be possible to implant up to 650 electrodes; hence, 650 dots were used to create images and performance studied under 0% dropout (650 dots), 25% dropout (488 dots) and 50% dropout (325 dots) conditions. It was observed that all the subjects under test were able to learn the given tasks and showed improvement in performance with practice even with a dropout condition of 50% (325 dots). Hence, if a cortical prosthesis is implanted in human subjects, they might be able to perform similar tasks and with practice should be able to adapt to dotted images even with a low resolution of 325 dots of phosphene.